Comparison of Symmetric Dimethylarginine (SDMA), Creatinine, and Cystatin C Level as Biomarkers of Chronic Kidney Disease in Diabetic Patients With and Without Microalbuminuria - Shah, Amir Asad; Haroon, Maryam; Gardezi, Shahnawaz Hassan; Zahid, Hiba; Javaid, Mian Adnan Aslam (Biological and Clinical Sciences Research Journal, 2025)
Diabetic kidney disease remains a major contributor to chronic kidney disease (CKD) morbidity. Earlier detection beyond serum creatinine alone is needed. Symmetric dimethylarginine (SDMA) and cystatin C have been proposed as sensitive markers of reduced glomerular filtration. Objective: To measure and compare the levels of symmetric dimethylarginine, creatinine and Cystatin C in diabetic patients with and without microalbuminuria as markers for diagnosis of chronic kidney disease Methods: This was a case-control study involving 110 diabetic patients with or without microalbuminuria who visited the Departments of Pathology at Nishtar Hospital, Multan Patients were divided into cases (diabetic patients with microalbuminuria) and controls (diabetic patients without microalbuminuria).5 mL blood sample was collected for random blood glucose level, HbA1C, renal function tests (urea & creatinine), SDMA and cystatin C. Results: Among cases (with microalbuminuria), the mean HbA1C (%), SDMA (µmol/L), serum creatinine (mg/dL), serum cystatin C (mg/L) and eGFR (ml/min/1.73m2) was 8.3± 2.1, 1.4 ±0.8, 0.9 ± 1.0, 0.02 ± 0.02 and 94.6 ± 41.2, receptively. Among controls (without microalbuminuria), the mean HbA1C (%), SDMA (µmol/L), serum creatinine (mg/dL), serum cystatin C (mg/L), and eGFR (ml/min/1.73m2) were 7.1 ± 2.4, 1.1 ± 0.9, 0.7 ± 0.4, 0.007± 0.005, and 108.0 ± 53.5, respectively. Conclusion: There were higher levels of SDMA, serum creatinine, and Cystatin C among diabetic patients with microalbuminuria than among patients without microalbuminuria.